Graphical Method for Synthesizing a Four-Bar Linkage with Specified Coupler Angular Reversal Positions - Buśkiewicz, Jacek (Engineering Transactions, 2026)
Graphical methods remain an important tool in the theory of mechanisms due to their ability to visually convey fundamental kinematic principles. They are particularly useful in the early design stages and in educational contexts, where intuitive understanding is essential. Among the applications of graphical synthesis methods, mechanisms that require a link to momentarily stop at specific angular positions – commonly referred to as angular reversal positions – are of particular interest. While various analytical and numerical methods exist for designing such mechanisms, they typically focus on dwell positions of rotational or translational links and rely on optimization techniques, often at the cost of geometric transparency. This paper presents a graphical synthesis method for a four-bar linkage designed to achieve two prescribed positions at which the coupler reverses its direction of rotation. This specific problem has not been previously addressed in the literature. It arises in mechanisms used for emptying containers, where the coupler carries the container and must instantaneously pause at two distinct angular positions to ensure stable discharge. Unlike many graphical methods, which may involve ambiguity due to trial-and-error selection of geometric parameters, the proposed technique ensures a unique and geometrically consistent solution while also allowing the Grashof conditions to be satisfied. This contrasts with many numerical methods, where constraint verification is often deferred until the final stages. The construction proposed here is both practically relevant and introduces a novel graphical approach, broadening the scope of synthesis methods to encompass mechanisms exhibiting link dwells in planar motion and reaffirming the relevance of graphical approaches.